Submarine landslide triggered by volcanic eruption recorded by in situ hydrophone - Chadwick, W W; Dziak, R P; Haxel, J H; Embley, R W; Matsumoto, H (Geology, 2012)
NW Rota-1 is a submarine volcano in the Mariana volcanic arc that is notable as the site where underwater explosive eruptions were first witnessed in A.D. 2004. After years of continuous low-level eruptive activity, a major landslide occurred at NW Rota-1 in August 2009, triggered by an unusually large eruption that produced 10 times the acoustic energy of the background level of activity. An anomalous earthquake swarm preceded the eruption, suggesting that the sequence started with a magmatic intrusion and associated faulting beneath the volcano. We quantify the size and extent of the landslide using bathymetric resurveys and interpret the timing of events using data from an in situ hydrophone. This is the first instrumental documentation of an earthquake-eruption-landslide sequence at a submarine volcano, and illustrates the close interaction between magmatic activity and mass wasting events in the growth of undersea arc volcanoes.
Keywords: ROV Jason (Remotely Operated Vehicle)